Exploring EFL Teachers’ First Experience with Online Assessment at Mohamed Lamine Debaghine Setif-2 University - Senouci , Madiha (Milev Journal of Research and Studies, 2022)
The current study aims to explore teachers’ experience with online assessment. It seeks to investigate EFL teachers’ perceptions, practices and challenges of online assessment at Mohammed Lamine Debaghine University- Setif2. To achieve the purpose of this study, an exploratory design is followed. For data collection, a semi-structured adapted questionnaire is administered to 34 EFL teachers who are selected based on a convenience sampling technique. The data are analyzed quantitatively using SPSS.22 and qualitatively via thematic analysis. The results reveal that teachers have positive perceptions of using online assessment to evaluate students’ progress. However, the findings indicate that online assessment practices are not well implemented; and teachers tend to focus on-open ended practices with written assignments and research projects as the major strategy for their online assessment practice. Another finding reveals that teachers are facing a number of challenges when implementing online assessment among which are: the potential risk of students cheating, the poor or absence of internet connection, the difficulty of assessing students online in listening or speaking classes and teachers’ unfamiliarity with ICT’s. Accordingly, a number of pedagogical implications is offered.